ATTRIBUTIVE PHRASES IN TRADITIONAL AND COGNITIVE ASPECTS OF LEARNING ENGLISH LANGUAGE - Mukhamedova , Lola Djurayevna (Innovative Development in Educational Activities, 2023)
Modern people cannot imagine a world without the use of language. “We pass absolutely all the knowledge that we receive through the network of language,” and then we transmit it to each other “as a result of subject-specific practical activity”. Moreover, literally every time, uttering this or that word, phrase or sentence, a person, as if from a blank slate, is engaged in the generation of meanings, choosing the means of their representation. One of the means of representing generated meanings about any object of reality at the language level is an attributive phrase.